An Adaptable Physiological Model of Endocytic Megalin Trafficking in Opossum Kidney Cells and Mouse Kidney Proximal Tubule. Issue 6 (7th September 2022) - Shipman, Katherine E; Long, Kimberly R; Cowan, Isabella A; Rbaibi, Youssef; Baty, Catherine J; Weisz, Ora A
Abstract: The cells that comprise the proximal tubule (PT) are specialized for high-capacity apical endocytosis necessary to maintain a protein-free urine. Filtered proteins are reclaimed via receptor-mediated endocytosis facilitated by the multiligand receptors megalin and cubilin. Despite the importance of this pathway, we lack a detailed understanding of megalin trafficking kinetics and how they are regulated. Here, we utilized biochemical and quantitative imaging methods in a highly differentiated model of opossum kidney (OK) cells and in mouse kidney in vivo to develop mathematical models of megalin traffic. A preliminary model based on biochemically quantified kinetic parameters was refined by colocalization of megalin with individual apical endocytic compartment markers. Our model predicts that megalin is rapidly internalized, resulting in primarily intracellular distribution of the receptor at steady state. Moreover, our data show that early endosomes mature rapidly in PT cells and suggest that Rab11 is the primary mediator of apical recycling of megalin from maturing endocytic compartments. Apical recycling represents the rate-limiting component of endocytic traffic, suggesting that this step has the largest impact in determining the endocytic capacity of PT cells. Adaptation of our model to the S1 segment of mouse PT using colocalization data obtained in kidney sections confirms basic aspects of our model and suggests that our OK cell model largely recapitulates in vivo membrane trafficking kinetics. We provide a downloadable application that can be used to adapt our working parameters to further study how endocytic capacity of PT cells may be altered under normal and disease conditions. Graphical Abstract: